1995
DOI: 10.1037/0735-7036.109.1.68
|View full text |Cite
|
Sign up to set email alerts
|

Sibling effects on the behavior of infant mouse litters (Mus domesticus).

Abstract: We investigated whether the number of same- or other-sex littermates had a graded effect on the occurrence of early solitary play and social play by mouse (Mus domesticus) family units. Sixty litters, reduced at birth to 5 different sex ratios (6 males, 5 males and 1 female, 3 males and 3 females, 1 male and 5 females, and 6 females) were scored in 15-min sessions on postnatal Days 18 and 21. An increasing trend with age was found for run, pounce, popcorn, self-groom, and explore episodes. Type of family unit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 58 publications
2
38
0
Order By: Relevance
“…Some evidence of increased exploration rates comes from the lack of selectivity of the interactions: females that interacted more did so with a greater number of different partners. Moreover, exploration is a male-like behaviour and masculinized females are more exploratory than non-masculinized females [25]. Exploration might trigger higher dispersal rates, and previous studies found that masculinized females are more likely to disperse [5,26].…”
Section: Discussionmentioning
confidence: 99%
“…Some evidence of increased exploration rates comes from the lack of selectivity of the interactions: females that interacted more did so with a greater number of different partners. Moreover, exploration is a male-like behaviour and masculinized females are more exploratory than non-masculinized females [25]. Exploration might trigger higher dispersal rates, and previous studies found that masculinized females are more likely to disperse [5,26].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, there is evidence that suggests that prolonged postnatal development affects a wide range of neurobehavioral systems, and not just play. For example, mice (Mus domesticus) have only a rudimentary form of social play compared to rats (Pellis & Pasztor, 1999), although the solitary, locomotor forms of play in mice seem to be as complex as that in rats (Laviola & Alleva, 1995;Pellis & Pellis, 1983;Terranova, Laviola, & Alleva, 1993). Not only do mice have a rudimentary pattern of social play but they also are simpler than rats for a wide range of social and nonsocial cognitive capacities (Whishaw, Metz, Kolb, & Pellis, 2001).…”
mentioning
confidence: 97%
“…Play behaviour varies among litters as a function of litter size, litter sex ratio, and nutritional state or weight (Caro 1981;Laviola & Alleva 1995;D'Eath & Lawrence 2004;Nunes et al 2004). Such interlitter variability is also correlated with major differences in adult behaviours, including aggressiveness, sexual behaviour, maternal behaviour and behavioural, hormonal and neurochemical responses to stress and novelty (Sharpe et al 1973;Namikas & Wehmer 1978;Laviola & Terranova 1998;D'Eath & Lawrence 2004).…”
Section: Article In Pressmentioning
confidence: 99%